PENGARUH PENERAPAN PROGRAM K3 DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PABRIK KELAPA SAWIT (PKS) PT. PERKEBUNAN NUSANTARA V UNIT LUBUK DALAM KAB. SIAK - Illahi, Kurnia; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Occupational Safety and Health (OSH) as Variable (X₁), Work Discipline as variable (X₂) and Employee Productivity as variable (Y).The method in this research is quantitative with SPSS program, where the sample used is the production employee as much as 100 respondents. The amount can already represent the population. Techniques of collecting data through questionnaires, interviews and observations directly to the field.The result of the research concluded that the variable of Occupational Safety and Health (OSH) has a significant effect on employee work productivity, and work discipline has a significant effect on employee work productivity.Keywords: Occupational Safety and Health (OSH), Work Discipline, Employee Productivity